Acceleration and incubation - approaches to youth agripreneurship in West Africa - Odetayo, Wole (Technical Centre for Agricultural and Rural Cooperation, 2018)
Wole Odetayo, the Executive director of Wennovation Hub in Nigeria, explains the difference between acceleration and incubation.